Prognostic significance of chromosomal abnormalities at relapse in children with relapsed acute myeloid leukemia: A retrospective cohort study of the Relapsed AML 2001/01 Study. Issue 1 (17th September 2021) - Klein, Kim; Beverloo, H. Berna; Zimmermann, Martin; Raimondi, Susana C.; von Neuhoff, Christine; de Haas, Valérie; van Weelderen, Romy; Cloos, Jacqueline; Abrahamsson, Jonas; Bertrand, Yves; Dworzak, Michael; Fynn, Alcira; et al.
Abstract: Background: In addition to treatment response, cytogenetic and molecular aberrations are the most important prognostic factors in children with de novo acute myeloid leukemia (AML). However, little is known about cytogenetics at the time of relapse. Methods: This international study analyzed the prognostic value of cytogenetic profiles and karyotypic changes in pediatric relapsed AML in relation to the probability of event‐free (pEFS) and overall survival (pOS). For this purpose, cytogenetic reports from all patients registered on the Relapsed AML 2001/01 Study were reviewed and classified. Results: Cytogenetic information at relapse was available for 403 (71%) of 569 registered patients. Frequently detected aberrations at relapse were t(8;21)(q22;q22) ( n = 60) and inv(16)(p13.1q22)/t(16;16)(p13.1;q22) ( n = 24), both associated with relatively good outcome (4‐year pOS 59% and 71%, respectively). Monosomy 7/7q−, t(9;11)(p22;q23), t(10;11)(p12;q23), and complex karyotypes were associated with poor outcomes (4‐year pOS 17%, 19%, 22%, and 22%, respectively). Of 261 (65%) patients for whom cytogenetic data were reliable at both diagnosis and relapse, pEFS was inferior for patients with karyotypic instability ( n = 128, 49%), but pOS was similar. Unstable karyotypes with both gain and loss of aberrations were associated with inferior outcome. Early treatment response, time to relapse, and cytogenetic profile at time of relapse were the most important prognostic factors, both outweighing karytoypic instability per se. Conclusion: The cytogenetic subgroup at relapse is an independent risk factor for (event‐free) survival. Cytogenetic assessment at the time of relapse is of high importance and may contribute to improved risk‐adapted treatment for children with relapsed AML.